Principles of Agent-Oriented Programming - Batista, André Filipe de Moraes; Marietto, Maria das Graças Bruno; Botelho, Wagner Tanaka; Kobayashi, Guiou; Alves, Brunno dos Passos; Castro, Sidney de; Ruas, Terry Lima (IntechOpen, 2011)
None